Calculation of Shield Tunneling Response Based on Subloading Cam-Clay Model - LI Liang; LU Yong; FAN Cunxin; GUO Bing; LI Anyong (Chengshi guidao jiaotong yanjiu)
［Objective］During shield tunneling in water-rich soft strata, ground deformation is often influenced by the combined effects of soil strength, deformation, and permeability characteristics. The time effect caused by permeability characteristics may further impact the surrounding environment. Therefore, it is necessary to use a reasonable constitutive model to conduct stress-seepage coupling calculations, and study the ground deformation response induced by shield tunneling in saturated silty clay. ［Method］Taking the Yuchijing Station-Baihetan Station interval on Suzhou Rail Transit Line 11 as an example, a subloading Cam-Clay model that reflects the state correlation of soil mechanical properties is adopted, and combined with a stress-seepage coupling finite element program, to calculate and analyze the land subsidence and pore water pressure response patterns induced by shield tunneling in saturated silty clay. The results are compared with the field-measured engineering data. ［Result & Conclusion］The stress-seepage coupling calculation based on the subloading Cam-Clay model can effectively reproduce the effects of shield tunneling. Shield tunneling in saturated silty clay can easily induce ground deformation, which is significantly affected by changes in the excavation face pressure. The excessive excavation face pressure often induces ground heave. Shield construction causes extrusion disturbance to the soil in front of the excavation face, which in turn induces the evolution of excess pore water pressure in the surrounding soil layers. This is also the intrinsic mechanism for the time effect of ground deformation.